Langmuir probe characterization of laser ablation plasmas - LUNNEY, JAMES GERARD (Elsevier, 2009)
For laser ablation plumes that are significantly ionized, Langmuir probes have proved to be a useful tool for measuring the plume shape, ion energy distribution, and electron temperature. Typically in laser ablation plasmas the flow velocity is supersonic, which complicates the interpretation of the current-voltage probe characteristic. In this paper we describe some recent developments on the application of Langmuir probes for laser ablation plume diagnosis. We have investigated the behavior of the probe when it is orientated perpendicular, and parallel, to the plasma flow, and show how an analytical model developed for plasma immersion ion implantation, can quantitatively describe the variation of the ion current with probe bias for the case when the plasma flow is along the probe surface. The ion signal recorded by a probe in the parallel position is proportional to the ion density and the square root of the bias voltage. It is shown that the current varies as mi ?1/2 so that by comparing the ion signals from the parallel and perpendicular positions it is possible to estimate the mass of the ions detected. We have also determined the temporal variation of electron temperature. A planar probe oriented parallel to the plasma flow, where the ion current due to the plasma flow is eliminated, gives a more reliable measurement of Te(<0.6 eV). The measured Te is consistent with the measured ion current, which is dependent on Te when the time taken for an element of plasma to traverse the probe is longer than the time taken for the matrix ion sheath extraction phase.
PUBLISHED
Keywords: Physics